"Not in our water!": Environmental resistance in rural Wisconsin. (October 2020) - Driscoll, Adam; Theis, Nicholas
Abstract: Concentrated Animal Feeding Operations (CAFOs) are known to have a wide range of negative impacts upon nearby residents and communities. Therefore, the siting of such operations in economically underdeveloped rural communities is an important environmental justice issue. This study explores the environmental conflict that surrounded a proposed CAFO in Bayfield County, Wisconsin. In this struggle, an outside corporation attempted to site a new CAFO in a community that was highly divided on the issue. We draw complementary insights from the environmental justice, stakeholder theory, and rural studies literatures to explain how the opponents of the CAFO were ultimately able to successfully resist the unwanted land use. This theoretical framework treats the formation of environmental inequalities as a process of conflict among diverse parties in which the potentially impacted communities may strongly influence the eventual outcome. Through interviews with key stakeholders and analysis of local and state media sources, we examine the primary points of contention within the local community along with the relative claims making and discursive strategies employed by each side. The findings of this study imply that how rural communities construct their identity and define potential environmental hazards are central to deciding environmental conflicts. Highlights: We analyze the discourses surrounding the conflict over a proposed CAFO in rural Wisconsin. Circumstances unique to rural spaces and people influence their discursive strategies. Rural communities may have more agency than previously recognized to fend off unwanted land uses. Struggles associated with rural environmental injustice can center on negotiations over meaning and understanding.